Indian Scenario : Certification of Forest Management and Legality of Wood and Wood Products from Agroforestry - Singh, Madan Prasad; Humachadakatte; Swamy, Ramachandra; Prabuddha; Purushotham, Prathima (Indian Forester, 2023)
Growing concern about sustainable forest management vis-Ã -vis deforestation especially in tropical countries has led to the introduction of market mechanism known as Forest Certification. It ensures customers of the forest products that, items they purchase have been originated from sustainably managed forest areas. International certifying agencies have laid down the principles /standards for forest certification which are generally suited for large privately managed forests and it would also add considerable amount to the cost of timber production. Therefore, it acts as a trade barrier especially to the export-oriented wood-based industries of developing countries. In Indian context, around 90 per cent of the raw material (timber) for these industries is supplied by agroforestry sector which is contrary to other timber exporting countries. The forest areas in India are sustainably managed by the government, based on the provisions of approved working plans. Therefore, in this paper, it is propounded that India should have its own framework of forest certification based on the Criteria-Indicators developed through Bhopal India process and separate certification standards should be developed for the farm grown wood to ensure 'due diligence' in proving its legality and thereby boost agroforestry and income of small and marginal farmers.